The risk of non-traumatic myelopathy in time trial (TT) or downhill (DH) bike position - Sugiura, K.; Sugiura, M. (Journal of Sports Medicine & Doping Studies, 2017)
Non-traumatic and ischemic myelopathy, which may develop in cyclists using the TT or DH position, is a minor syndrome and a new concept of myelopathy in triathletes that physicians may encounter in cyclists who race. Some athletes develop neck pain, headache, and numbness of arms (hands) or legs when using the TT or DH position with neck extension and strained body. Not all instances of these symptoms are myelopathy, but a few cases may involve mild myelopathy. Because many athletes change riding position in cycling, there may be very few cases of complete myelopathy.